The Effectiveness of Teacher Training in Creating Web-Based Learning Media: An Analysis of Teacher Knowledge (Jurnal Pendidikan Fisika, 2024)
The background of this research is to produce professional teachers with digital competency through training in making web-based learning media. This study aims to analyze how effective the training on teachers' knowledge in generating web-based learning media is to produce professional teachers. This research used a quantitative study with the one-group pre-test/post-test design approach. This research was conducted by the 20 teachers at SMAN 2 Tondano who trained in making web-based learning media integrated by a project-based learning model (PjBL). Based on data analysis with the N-gain test, this study concludes that web-based learning media creation training on teachers at SMAN 2 Tondano has improved teacher knowledge in a medium category, with an average increase of 43%. The data has also been confirmed through a hypothetical test showing that the α